2016
DOI: 10.1001/jamaoto.2015.2687
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Quality Measures in Otolaryngology–Head and Neck Surgery

Abstract: As health care reimbursements based on pay-for-performance models become more common, there is an unprecedented demand for ways to measure health care quality and demonstrate value. Performance measures, a type of quality measure, are unique tools in a health care delivery system that allow objective monitoring of adherence to specific goals and tracking of outcomes. We sought to provide information on the development of quality measures in otolaryngology–head and neck surgery, as well as the goals of performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In this study, we also found the complication rate to be comparable with conventional thyroid surgery according to previously published data from our group (50)(51)(52)(53)(54). Quality assessment by comparing outcome indicators with established benchmarks (25)(26)(27) can be used to define the outcome of an intervention and measure an improvement in outcomes caused by a modification of a treatment or care process (55). We performed this quality assessment in this group of cases, showing that, even in the initial experience and beginning of the learning curve of robotic thyroid surgery in our department, we achieved all quality goals established for low acuity procedures.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we also found the complication rate to be comparable with conventional thyroid surgery according to previously published data from our group (50)(51)(52)(53)(54). Quality assessment by comparing outcome indicators with established benchmarks (25)(26)(27) can be used to define the outcome of an intervention and measure an improvement in outcomes caused by a modification of a treatment or care process (55). We performed this quality assessment in this group of cases, showing that, even in the initial experience and beginning of the learning curve of robotic thyroid surgery in our department, we achieved all quality goals established for low acuity procedures.…”
Section: Discussionsupporting
confidence: 76%
“…This renewed emphasis can be seen at nearly every level, ranging from the solo provider who reviews their individual practice with quality improvement in mind, to the third‐party payer who institutes a program that links payment to quality outcomes. Implicit in any effort that focuses on quality improvement is the understanding that quality can actually be measured and that references exist that allow one to determine if an individual or entity is underperforming, overperforming, or performing at an expected level as compared to that reference . A recent review of quality measurement for chronic rhinosinusitis (CRS) highlighted that all currently collected quality measures were process metrics and specifically lacked assessment of patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have sought to generalize metrics across specialties; these must be customized to represent higher levels of care. 1-3…”
mentioning
confidence: 99%